APLIKASI PRESENSI PERKULIAHAN MAHASISWA MENGGUNAKAN QR-CODE DAN LOCATION BASED SERVICE BERBASIS ANDROID - Siregar, Fadhilah Anisah; Suendri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Technological advancements have had a significant impact on life, including work and education. In the era of globalization, technological development is very important, including in the learning process. Attendance is an important aspect of student performance assessment. However, the manual timekeeping system has problems such as fraud, low accuracy, and data entry errors. This study aims to design conferencing applications that use QR codes and location-based services (LBS) to simplify and accelerate attendance management. The development method used is prototyping, which allows interaction between developers and users. This application is built using App Inventor on Android operating system, allowing to scan QR codes for class attendance. Attendance data is automatically stored in Google Drive for recording and report generation that teachers can flexibly access. The application of this technology is expected to increase the efficiency and accuracy of attendance as well as the quality of the learning process in higher education institutions.